Evaluations of microvascular density by optical coherence tomography, angiography, and function by multifocal electroretinography of the macular area in eyes with branch retinal artery occlusion - Igawa, Yuro; Amaki, Haruna; Kanno, Junji; Tachibana, Midori; Konno, Satomi; Yoshikawa, Yuji; Matsumoto, Soiti; Shoji, Takuhei; Makita, Jun; Shinoda, Kei (Frontiers in Ophthalmology, 2023)
The purpose of this study was to determine the density of the microcirculation and the function of the macular area of eyes with a branch retinal artery occlusion (BRAO), and to determine whether they are significantly correlated. The optical coherence tomography angiographic (OCTA) and multifocal electroretinographic (mfERG) findings of 7 eyes of 6 patients (3 men, 3 women) were studied. The mean age of the patients was 71.7±10.6 years. The OCTA examinations were made with volume scans of 3 x 3 and 6 x 6 mm squares centered on the fovea. The macular vessel densities (mVD) in the superficial retinal layer (SRL) and deep retinal layer (DRL) were measured for the superior and inferior halves of 3 X 3 mm and 6 x 6 mm diameter concentric circles. The mfERGs were recorded with targets set to stimulate the focal areas of the retina corresponding to the areas examined by OCTA. The OCTA examinations showed that the mVD of the 3 mm concentric circle in the SRL was significantly lower on the affected side than on the unaffected side (P = 0.022).No such difference was observed in the DRL. The N1 amplitude of the 20.2° concentric circle and the N1-P1 amplitude of the 10.1° concentric circle of the mfERGs were significantly smaller on the affected side than on the unaffected side (P=0.047 and 0.031). A significant positive correlation was found between the mVD in the 6 mm concentric circle in the DRL and the P1-N2 amplitude of 20.2° concentric circle (ρ= -0.929, P = 0.003). These findings indicate that OCTA images may be able to show changes in the density of the retinal macular microcirculation, and the mfERGs may be able to show alterations of the function of the macular area of eyes with BRAO. A layer-by-layer analysis of the local retinal microcirculation and function should help in determining the pathogenesis of BRAO.